Asystole Following Concomitant Intravenous Administration of Neostigmine and Dexmedetomidine in a Patient With Acute Colonic Pseudo-Obstruction. (August 2022) - Bell, Carolyn Magee; Procter, Levi D.; Parli, Sara E.
Acute colonic pseudo-obstruction (ACPO) is a condition characterized by acute dilation of the large bowel without evidence of mechanical obstruction that occurs in a variety of hospitalized patients with many predisposing factors. Management includes supportive care and limitation of offending medications with mainstays of treatment of neostigmine administration and colonic decompression. We report the case of a critically ill patient with ACPO who experienced bradycardia and a brief episode of asystole when receiving concomitant dexmedetomidine and neostigmine infusions but who later remained hemodynamically stable when receiving propofol and neostigmine infusions. The bradycardia and associated hemodynamic instability experienced while on dexmedetomidine and neostigmine infusions were rapidly corrected with atropine and cessation of offending agents. Because ACPO is encountered frequently and the use of dexmedetomidine as a sedative agent in the ICU is increasing, practitioners should be aware of the additive risk of bradycardia and potential for asystole with the combination of neostigmine and dexmedetomidine. Electronic drug interaction databases should be updated and drug information sources should include a drug-drug interaction between dexmedetomidine and neostigmine to reduce the likelihood of concomitant administration.